Seismic potential in and around the Sichuan basin from the dense GNSS network - Xu, Rui; Chen, Cong; He, Fuxiu; Liu, Xuemei (Frontiers in Earth Science, 2024)
The Sichuan basin (SCB) is situated at the southeastern edge of the Tibetan Plateau where widespread seismicity haves occurred. In the past decades, seismic events occurred in and surrounding around SCB has have been responsible for more than 100 thousand casualties. To quantify the present-day seismic hazard of this region, especially the densely populated Chengdu-Chongqing economic zone (CCEZ), in this study, we develop a probabilistic earthquake forecast model using regional strain rates derived from 187 Global Navigation Satellite System (GNSS) horizontal velocities, of which 102 velocity vectors are first released. The second invariant of the strain rate tensor suggests that the Mianning Shimian County and its surroundings are exposed to the highest seismic hazard in and around SCB. The second most dangerous area is located between 103-105°E and the Chongqing area is the least dangerous. The principal strain rate axes interior of the Sichuan basin suggests that this region is experiencing broad broad-scale extension, which according to our knowledge, is first revealed by our dense GNSS network. The cComparison between the cumulative histograms of the second invariant of geodetic strain rate and earthquake count suggest indicates that the geodetic strain rates in this region can be serve as a reliablegood forecaster predictor of locations of M≥6 earthquake locationss. Thus, we proceed to calculate the total seismic moment anticipated for the entire area within the next 30 years.We therefore further estimate the accumulated seismic moment of the whole region in the coming 30 years.